Ku początkom Poznania – nowo odkryta osada z zarania wczesnego średniowiecza - Pawlak, Paweł (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The paper discusses the remains of an early medieval settlement, dating from the late 7th to the end of the 9th century. Ten features and movable finds related to this period were studied, and included three semi-dugout dwellings, a single pit used either for smoking, roasting or making wood tar and four hearths, while the purpose of two features could not be determined. Among the movable finds were pottery, animal bones, roasted fragments, daub lumps, a whetstone and grindstones, as well as an iron spur with catches hooked inside.